A straightforward approach to N-substituted-2H-indazol-2-amines through reductive cyclization. Issue 16 (19th April 2017) - Schoene, Jens; Bel Abed, Hassen; Christmann, Mathias; Nazaré, Marc
Graphical abstract: Highlights: A two-step, one-pot reaction to access N -substituted-2 H -indazol-2-amine derivatives has been elaborated. A diverse set of analogues was obtained by a sequential in-situ hydrazone formation and reductive cyclization. This allows the rapid generation of "drug-like" compound libraries of novel N -amino heterocycles. Abstract: A versatile two-step, one-pot reaction to access N -substituted-2 H -indazol-2-amine derivatives has been elaborated. A diverse set of analogues was obtained by a sequential hydrazone formation and reductive cyclization in moderate to good yields from readily available starting materials. The strategy tolerates a broad range of substitutions pattern and functional groups allowing further derivatizations.